An Analysis of Build-Up Growth Impacts to Water Stream Line of Motorway-6 Project End Point in Muang District of Nakhon Ratchasima Province - Patiwat Littidej (Warasan Witthayasat Lae Theknoloyi Mahawitthayalai Mahasarakham, 2019)
Due to rapid growth of Nakhon Ratchasima province. Land use and Land cover change (LULC) change takes place in surrounding end point of Motorway of Nakhon Ratchasima municipality and its vicinity, various types of environmental impacts occur in the area. Main objectives of the study are to assess built-up growth rate and mapping from transition matrix of satellite image during 2013-2016. Results of the built-up growth prediction of land cover in 2021 using CA-Markov showed that Motorway road was the strongest predictor variable and the most vulnerable landuse lost was miscellaneous. Urban and built-up areas had continuously increased while agricultural and forest had continuously decreased. Urban growth pattern was linear strip development but its pattern was changed to be a scattered development. The simulated area results in a shorter flow of water in stream order 1 to 2. The direction of the flow of water away from the main river (Lamtaklong). However, the forecast of urban growth pattern remains problematic because the model performed with a relatively moderate predictive ability (60 %) at a spatial unit of 1 km. x 1 km. This application of the CA-Markov model demonstrated an ability to address a range of local planning issue, but spatial accuracy and variable selection were among the factors that must be further considered for practical application.